2018
DOI: 10.1016/j.rmed.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to lung function in bronchiectasis

Abstract: A comprehensive approach to lung function in bronchiectasis ABSTRACT Background: International guidelines recommend simple spirometry for bronchiectasis patients. However, pulmonary pathophysiology of bronchiectasis is very complex and still poorly understood. Our objective was to characterize lung function in bronchiectasis and identify specific functional sub-groups. Methods:This was a multicenter, prospective, observational study enrolling consecutive adults with bronchiectasis during stable sate. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 46 publications
2
47
0
4
Order By: Relevance
“…Recently, two studies confirmed the high prevalence of air trapping among patients with bronchiectasis. 33 , 34 Radovanovic et al 33 demonstrated the presence of air trapping in 70.2% of their sample, whereas an obstructive pattern was present in only 41.1%. This variability in the identification of patterns on pulmonary function testing can be explained by the different characteristics of the populations studied.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, two studies confirmed the high prevalence of air trapping among patients with bronchiectasis. 33 , 34 Radovanovic et al 33 demonstrated the presence of air trapping in 70.2% of their sample, whereas an obstructive pattern was present in only 41.1%. This variability in the identification of patterns on pulmonary function testing can be explained by the different characteristics of the populations studied.…”
Section: Discussionmentioning
confidence: 95%
“…Physiologically, bronchiectasis is classically characterised by obstructive air flow limitation. However, in a prospective multicentre study of 187 patients with bronchiectasis, only 41% had obstruction on spirometry, while 58% had a normal spirogram [48]. Another study of 277 patients found an obstructive pattern in 43%, and 28.7% had a restrictive or mixed pattern [49].…”
Section: Antithesis: Bronchiectasis Is Not a Diseasementioning
confidence: 97%
“…In this study, questions regarding generalisability come to mind. The median MRC dyspnoea score in the bronchiectasis patients was 3 on a 1-5 scale ("I walk slower than people of the same age on the level because of breathlessness or have to stop for breath when walking at my own pace on the level") [17], higher than in two large studies of unselected bronchiectasis patients, in which it was 2 [18] and 1 [19]. Thus the study patients may not be representative of the broader population of bronchiectasis patients.…”
mentioning
confidence: 75%